(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
The behavior ofÂ 2-ethoxycarbonyl-4H-3,1-benzoxazin-4-one and its behavior towards nitrogen nucleophiles namely, hydrazine hydrate, formamide, benzylamine, ethylamine, piperidine, ethanol amine, o-phenylenediamine, and glucosamine hydrochloride has been investigated. Also the reaction of 3-[aminoquinazolin-4(3H)-one-2-yl]formic acid hydrazide with aromatic aldehydes and phenylisothiocyanate has been discussed. The structure of the prepared compounds are elucidated using physical and spectral data like, FT-IR, 1HNMR, and mass spectroscopy.